Studies on compatibility of fluorescent Pseudomonas native isolates with fungicides and insecticides - PRIYANKA SINGH, PRAHLAD AHIRWAR*, A.R. WASNIKAR and PRIY (Indian Phytopathology, 2016)
The present study was conducted at Department of Plant Pathology, Jawaharlal Nehru Krishi Vishwa Vidyalaya, Jabalpur (M.P). All the four isolates I1 I2 I3 and I4 were tested for its biocontrol efficacy but only I2 posses high biocontrol efficacy (BCE). From the results it was evident that the highly potential with antagonistic effect was found I2 and was compatible with common fungicides and insecticides tested and showing inhibitory effect with test fungus also. Bio control agent Pseudomonas fluorescens was found suitable against soil borne plant pathogens tested viz., Fusarium oxysporum f.sp. ciceri, Sclerotium rolfsii, Rhizoctonia solani and efficacy for controlling these test fungus was not reduced in the presence of chemical fungicides and insecticides. Out of four namely fungicides Mancozeb, Carbendazim, Azoxystrobin and Hexaconazole; Azoxystrobin showing maximum inhibition of Rhizoctonia solani in PDA and Carbendazim showing maximum inhibition of Fusarium oxysporum f.sp. ciceri in King’s B medium. Out of four namely insecticides, Indoxacarb showing maximum inhibition of Sclerotium rolfsii in PDA and Imidacloprid showing maximum inhibition of Fusarium oxysporum f.sp. ciceri in King’s B. Pseudomonas fluorescens can in integrated with routinely used fungicides and insecticides against major soil borne pathogens.